Factors Influencing the Development of Logistics Services in Lao Cai Province, Vietnam - Dinh Hong Linh; Nguyen Thi Lan Anh; Nguyen Dac Dung (RIRAI Publisher, 2023)
This paper aims to investigate the main determinants of logistics development in Lao Cai Province, Vietnam. Logistics is an important service industry a country’s economic structure. It is also one of the topics that Lao Cai Provincial People's Committee was very interested in for the socio-economic development strategy for the period 2021-2025. The analysis of the factors influencing the development of logistics services in Lao Cai province has high theoretical and practical significance. The author used the exploratory factor analysis method through the primary data set from the survey results of 100 enterprises providing and using logistics services in Lao Cai Province in 2022 to analyse the factors affecting the development of this type of service in Lao Cai Province. The research results showed the role of logistics services in the socio-economic development of the province and the degree of influence of logistics services on the development of this service in Lao Cai Province in many different aspects. The degree of influence of the given factors are: (1) technical infrastructure (CSHTKT); (2) ability to access and mobilise capital of enterprises (HDV); (3) experience and management capacity of enterprises (NLQL); (4) facilities of logistics enterprises (CSVC); (5) human resourcess of enterprise (NNL); (6) factors of market economy (KTTT); and legal factors (PL). On this basis, the author proposed some policy recommendation for the development of logistics services in the province in the coming period.